2003
DOI: 10.3168/jds.s0022-0302(03)73728-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reducing Alfalfa Haylage Particle Size on Cows in Early Lactation

Abstract: The objective of this experiment was to evaluate effects of reducing forage particle size on cows in early lactation based on measurements of the Penn State Particle Separator (PSPS). Eight cannulated, multiparous cows averaging 19 ± 4 d in milk and 642 ± 45 kg BW were assigned to one of two 4 × 4 Latin Squares. During each of the 23-d periods, animals were offered one of four diets, which were chemically identical but included alfalfa haylage of different particle size; short (SH), mostly short (MSH), mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
155
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(201 citation statements)
references
References 33 publications
34
155
9
Order By: Relevance
“…In E2, total time spent eating and minutes per kilogram of NDFI were not different, whereas a trend for a quadratic effect of minutes per kilogram of DMI was observed; however, with small numerical differences this Suarez-Mena, Zanton and Heinrichs trend is probably not of physiological importance. Kononoff and Heinrichs (2003) and Teimouri Yansari et al (2004) using lactating cows observed a linear increase in eating time per day and minutes per kg of DMI and NDFI as (alfalfa haylage in the first study and alfalfa hay in the second) particle length increased. Nasrollahi et al (2012) also observed an increase of the same variables for greater alfalfa hay particle length, whereas Yang and Beauchemin (2006) observed no differences when barley silage particle length increased.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In E2, total time spent eating and minutes per kilogram of NDFI were not different, whereas a trend for a quadratic effect of minutes per kilogram of DMI was observed; however, with small numerical differences this Suarez-Mena, Zanton and Heinrichs trend is probably not of physiological importance. Kononoff and Heinrichs (2003) and Teimouri Yansari et al (2004) using lactating cows observed a linear increase in eating time per day and minutes per kg of DMI and NDFI as (alfalfa haylage in the first study and alfalfa hay in the second) particle length increased. Nasrollahi et al (2012) also observed an increase of the same variables for greater alfalfa hay particle length, whereas Yang and Beauchemin (2006) observed no differences when barley silage particle length increased.…”
Section: Resultsmentioning
confidence: 95%
“…Failure to detect differences in DMI has been reported in cows averaging 189 6 38 DIM (Beauchemin et al, 2003); 153 6 7 DIM (Leonardi and Armentano, 2003); 189 6 39 DIM (Yang and Beauchemin, 2006); and 175 6 21 DIM (Nasrollahi et al, 2012). In contrast, other studies with cows averaging 19 6 4 DIM (Kononoff and Heinrichs, 2003) and 81 6 15 DIM (Teimouri Yansari et al, 2004) observed an increase in DMI when forage particle length was reduced (reported DIM were at the beginning of the experiments). In E1, DMI increased numerically as particle length decreased but standard errors were high, which may be the reason for the failure to detect differences.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations